PENERAPAN SISTEM HEMAT ENERGI PADA GEDUNG MENARA PHINISI, KOTA MAKASSAR - Ratriana Said; Syafril Nanar; Burhanuddin Burhanuddin (Teknosains, 2020)
Global warming is an issue that is currently often discussed by many people. One of the causes of global warming can be seen from the use of quite a lot of electrical energy in a building or building. This pressures the architects to play a role in designing a building that can save energy by paying attention and utilizing the surrounding climate conditions. Energy saving architecture is a concept that is offered to reduce excessive energy use. The object under study is the phinisi tower by collecting descriptive qualitative data. The purpose of this research is to find out the concept of applying energy saving phinisi towers that we can see with designs that make better use of climate in the context of natural ventilation.